Realising the Potential of the Internet in Business - Katarína Kleinová; Zuzana Lušňáková (Polityki Europejskie, Finanse i Marketing, 2012)
Internet is probably now the most important technology. It is constantly growing and bringing new possibilities for its use. Every day, new users and services are added. Companies are therefore looking into the possibilities of how to use the Internet for their business activities. In the beginning, it was used to streamline communication. But now, with the emerging of websites it has come a time to consider its use also for other business activities. Own company website is not uncommon today and it is almost a necessity if a business wants to succeed in the fierce competitive environment. With well-designed page that includes the psychological elements, enterprise can use the Internet network as its advantage. Every company, regardless of its size, should have its own website through which it is able to communicate with its customers, both current and potential, but also with suppliers, subscribers and other partners. A professional and dynamic website can also be a powerful benefit for a small business that can bring new and exciting business opportunities.